Suitability for agroforestry implementation around Itombwe Natural Reserve (RNI), eastern DR Congo: Application of the Analytical Hierarchy Process (AHP) approach in geographic information system tool - Géant Basimine Chuma (Elsevier, 2021)
The choice of appropriate land use suitability based on specific environmental and socio-economic factors could ensure sustainable land resource management in rural areas. Different land use suitability assessment approaches exist and have been successfully applied for agroforestry systems, natural or semi-natural ecosystems. In this study, different land use suitability levels for agroforestry were assessed around the Itombwe Natural Reserve (RNI), eastern Democratic Republic of Congo (DRC). Information related to soil unity, topography, climate, road infrastructures, rivers, villages, land use and land cover were analyzed using the Analytical Hierarchy Process (AHP). Moreover, spatial analyses were conducted for determining the matrix that confronts adopted variables and their corresponding weights. After performing the analyses in ArcGIS 10.7, results allowed identifying four agroforestry suitability zones, ranging from very high (~29.2%), high (~22.3%), moderate (~34%) and low (~14.5%) suitable zones. Suitability classes varied with locations (districts). The zoning around the RNI and the produced suitability maps from this study provide a valuable resource for decision-making in targeting areas suitable for agroforestry, and thus, contribute in preserving the RNI from degradation related to inadequate anthropogenic practices.